The Cognitive Element Model of Reading Instruction. (3rd September 2020) - Peng, Peng; Goodrich, J. Marc
ABSTRACT: The science of reading emphasizes explicit skills‐based reading instruction to support students' reading acquisition. Yet, despite ample evidence of support, some students do not respond to such instruction adequately. To characterize why some students are not responsive to evidence‐based reading instruction and to inform the development of novel instructional approaches for improving responsiveness, cross‐disciplinary perspectives on cognitive and academic development are important. Based on the cognitive–academic bidirectional theory, on cognitive training transfer theory, and on various working memory–reading models, the authors propose a cognitive element model of reading instruction that provides a novel framework for considering how to embed supports for cognitive processes within evidence‐based reading instruction. Specifically, the element model emphasizes building reading fluency and comprehension/knowledge with explicit instruction. Working memory should not be considered a domain‐general construct in working memory training that aims to produce far‐transfer effects on reading outcomes. Instead of looking for far‐transfer effects, we should make outcomes (i.e., reading) near‐transfer tasks such that working memory training should be domain (material) specific, task paradigm specific, and strategy specific and assimilated within existing skill‐based reading activities. The authors review intervention studies with rigorous methodology and show promising effects of this framework. With the element model, the authors provide a foundation for considering how one can use extant knowledge of evidence‐based reading instruction together with knowledge of related skills in other domains (e.g., cognitive psychology) to maximize the efficacy of reading instruction for all students.